Single VDDDA-Based Lossy Inductance Simulator for Application to Sinusoidal Oscillator - Winai Jaikla; Surapong Siripongdee; Roman Šotner; Peerawut Suwanjan (My University, 2023)
This work presents the design of a new grounded lossy inductance simulator. The proposed circuit emulates an inductor in parallel with a negative resistor, making it applicable to the design of a sinusoidal oscillator. The proposed simulator comprises a voltage differencing differential difference amplifier (VDDDA), a resistor, and a grounded capacitor. The proposed active inductor necessitates no essential matching criteria for passive elements. The equivalent inductance and negative resistance can be controlled electronically. Moreover, the parallel RLC and negative resistance configuration-based sinusoidal oscillator is designed as an example of its application. The oscillation frequency and condition are adjusted orthogonally. The performance of the proposed simulator circuit and the sinusoidal oscillator is evaluated using Pspice simulation and experimentation with VDDDA built from ICs AD830 and LM13700. The simulation and experimental results validate the behavior of the theory.
Keywords: Analog and Mixed-Signal Circuit Design; Radio Frequency Integrated Circuit Design; Advancements in PLL and VCO Technologies